Carbon and nitrogen cycling in an urban constructed technosol: The artist-led carbon sponge pilot study - Sara Perl Egendorf; Maha Deeb; Brooke Singer; Nkwi Flores; Marisa Prefer; Zhongqi Cheng; Peter Groffman (Geoderma, 2025)
Urban sustainability initiatives rely on healthy soils, and increasingly turn to constructed soils or constructed Technosols (CTs) to create green spaces, green infrastructure, and urban agriculture. However, CTs must be better understood, particularly in terms of their nutrient dynamics, to optimize their ecological functions. In the Carbon Sponge pilot study, located at the New York Hall of Science in Queens, NY, USA, our objective, through an artist-led collaboration, was to evaluate the effects of different plant communities on CT formation and carbon (C) and nitrogen (N) cycling. The artistic processes were rooted in social practice, focused more on practical outcomes than aesthetics. We constructed soils from excavated glacially-deposited sediments from the NYC Clean Soil Bank and urban municipal composts at a 2:1 vol:volume (v:v) ratio, and created 24 beds under 8 different planting regimes: control (bare, no plants); sunflowers; edibles (ground cherries and okra); cover crop mixture; and each of their combinations. We found that soils changed significantly over the study duration of 21 months (p = 0.001), particularly in terms of microbial biomass N content, an index of internal soil N cycling processes; the presence of sunflowers increased soil C and ammonium; and the presence of cover crop mixtures increased nitrate and ammonium. Over time, we observed an increase in microbial biomass C and N content and a decline in microbial respiration, suggesting the development of a soil microbial community that actively cycles C and N. Diverse planting combinations enhanced microbial development, yet all plants thrived in CTs, demonstrating their suitability for urban agriculture and horticulture, while enhancing ecosystem services and facilitating art-and-community-based initiatives.